IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENGEMBANGKAN KOMPETENSI KEWARGANEGARAAN DIGITAL: STUDI KASUS SDN KEMANTREN 1 - Lailatun Nazilah; Nurul Aini; Akhwani Akhwani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the low level of digital citizenship competence among fifth-grade students at SDN Kemantren 1, particularly amid negative digital phenomena such as cyberbullying, hoax dissemination, and social media misuse. This study aims to describe the implementation of Pancasila Education learning in developing three elements of students' digital citizenship competence: digital communication, digital literacy, and digital rights and responsibilities. A qualitative approach with a case study design was employed. Data were collected through teacher interviews, classroom observations of teachers and students, and documentation studies, then analyzed through data reduction, data display, and conclusion drawing, with source triangulation to ensure data credibility. The results show that implementation was carried out through the use of a smart TV and smartphones to access digital learning media (earth3dmap, padlet, wayground), the integration of Pancasila values into the